OPTIMIZATION OF COMMERCIAL BUILDING ENVELOPE WITH BUILDING-INTEGRATED PHOTOVOLTAIC (BIPV) IN VERTICAL FACADES WITH CONSIDERATION OF ENERGY CONSUMPTION AND THERMAL COMFORT - Mario Jeremi, Pokki
Energy consumption in buildings contributes 40% to global energy use and increases by 8-10% every 5 years. Indonesia, with its tropical climate, has significant potential for solar energy, making solar panels an ideal solution for urban buildings The direct installation of PV panels on the facades needs to be considered for commercial buildings, especially office buildings. Building-Integrated Photovoltaic (BIPV) is a relevant solution as it not only provides cost savings but also enhances architectural appeal. BIPV can be installed on both roofs and building facades. However, roof installations face limitations in terms of space, so the use of building facades can be considered. Facade installations present their own challenges, namely their impact on energy consumption performance and thermal comfort in buildings. In this research, a study and analysis were carried out for the implementation of the BIPV window in Jakarta using simulation method. The stages of this research are modelling simple building with PV—paired windows. Furthermore, simulations were carried out using Grasshopper software on Rhinoceros with variations in building envelope variables (WWR, site ratio, and BIPV orientation) to determine energy consumption performance and thermal comfort. The energy consumption performance indicator used is the Energy Use Intensity (EUI) metric and thermal comfort performance is reviewed based on the Predicted Mean Vote (PMV) metric with Percentage Comfort Hour (PCH) as the output. The results showed that the site ratio and orientation had a more significant effect on energy consumption performance and thermal comfort compared to WWR due to the shadows generated by the BIPV. Optimization results considering the performance of energy consumption, thermal comfort, and PV production show that the building model with a site ratio of 1:2, WWR of 40%, and bilateral PV installation on the south and north sides has optimal results compared to other variations.